2005
DOI: 10.1063/1.1888043
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Pt–Ag and Pd–Ag nanoparticles

Abstract: We report studies of bimetallic nanoparticles with 15%–16% atomic crystal parameters size mismatch. The degree of alloying was probed in a 2-nm Pt core (smallest attainable core size) of Pt–Ag nanoparticles (completely immiscible in bulk) and 20-nm-diameter Pd–Ag nanowires (completely miscible in bulk). Particles were synthesized radiolytically, and depending on the initial parameters, they assume spherical or cylindrical (nanowire) morphologies. In all cases, the metals are seen to follow their bulk alloying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 37 publications
0
39
2
Order By: Relevance
“…Ag is believed to be present on the surface because XRD measurements do not indicate the formation of a PtAg alloy, consistent with their complete immiscibility in the bulk [48]. Lahiri et al [49] have shown that Pt and Ag do not alloy at the nanoscale (2 nm Pt core particle), but rather form Ag-Pt coreshell nanoparticles. The deposition and growth of Ag adlayers on Pt(111) leads to monolayer confined mixing, i.e.…”
Section: Characterization and Ethylene Hydrogenation Studies Of Pt/sbmentioning
confidence: 86%
“…Ag is believed to be present on the surface because XRD measurements do not indicate the formation of a PtAg alloy, consistent with their complete immiscibility in the bulk [48]. Lahiri et al [49] have shown that Pt and Ag do not alloy at the nanoscale (2 nm Pt core particle), but rather form Ag-Pt coreshell nanoparticles. The deposition and growth of Ag adlayers on Pt(111) leads to monolayer confined mixing, i.e.…”
Section: Characterization and Ethylene Hydrogenation Studies Of Pt/sbmentioning
confidence: 86%
“…The picture of alloying between Pt and Ag is not so clear, and studies have shown that phase diagrams for alloys can change with particle size 43 . In two separate Xray absorption fine structure (XAFS) studies, no alloying was observed for a Pt-Ag catalyst, even for particle sizes down to 2 nm 44,45 . Pt-Ag bimetallic NP systems have produced Pt(core)/Ag(shell) 46 and also Ag(core)/Pt(shell) 47 structures as indicated by UV-Vis spectroscopy combined with modeling based on Mie theory.…”
Section: Ethylene Hydrogenation On Unetched and Etched Pt(shape)/sba-15mentioning
confidence: 99%
“…The referred data are from: solid circles, [15] solid squares, [16] solid prisms, [46] solid triangles, [47] open circles, [48] open triangles, [49] open squares [50] and open prisms [51] (sizes are estimated from the TEM images). [32] All the solid symbols denote the compositions and sizes for the particles that have been alloyed, while all the open symbols represent that for non-alloyed particles.…”
mentioning
confidence: 99%